218k views
1 vote
Let f() = 3x - 1 and g(x) = 2x + 3 and find f(g(3))

Select the correct

response

f(g(3)) = 21

f(g(3)) = 19

f(g(3)) = 26

f(g(3)) = 17

Let f() = 3x - 1 and g(x) = 2x + 3 and find f(g(3)) Select the correct response f-example-1
User MillsJROSS
by
4.7k points

2 Answers

5 votes
plug in 3 for g(x) which is 9 then plug in 9 for f(x) which is 26
User Andrei Avram
by
5.4k points
1 vote

Answer:

f(g(3)) = 26

Explanation:

f(g(3))

g(3) = 2x + 3

= 2(3) + 3

= 6 + 3

= 9

f(9) = 3x - 1

= 3(9) - 1

= 27 - 1

= 26

User Roger Cruz
by
5.7k points